The Behavior of Reinforced Concrete Beams with Various Carbon Fiber Retrofitting Methods in Enhancing Stiffness - Zai, Eben Oktavianus; Purba, Luki Hariando (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2025)
This study investigates the effectiveness of Carbon Fiber Reinforced Polymer (CFRP) sheets and rods in improving the structural performance of reinforced concrete beams. Three beam specimens were tested: a control beam (BN), a beam reinforced with CFRP rods (BTC), and a beam reinforced with CFRP sheets (BLC). The experimental evaluation focused on key parameters, including first crack load (Pcrack), yield load (Pyield), maximum load (Pmax), and deflections at critical points. The stiffness of the beams was assessed at both the cracking stage (Kcrack) and the yielding stage (Kyield). The results demonstrate that the beam reinforced with CFRP sheets (BLC) exhibited the highest improvements in stiffness, with an increase of 184.89% in Kcrack and 221.21% in Kyield compared to the control beam (BN). The CFRP rod-reinforced beam (BTC) also showed enhanced performance, but to a lesser extent, with increases of 72.69% in Kcrack and 64.78% in Kyield compared to BN. The data reveals that BLC significantly reduces deflection and enhances load-bearing capacity, particularly in resisting initial cracking and yielding. The discussion highlights that CFRP sheets provide superior stiffness improvement compared to CFRP rods, making them more suitable for applications where increased stiffness and reduced deflection are critical. While CFRP rods effectively increase the ultimate load capacity, their impact on stiffness is less pronounced than CFRP sheets. In conclusion, CFRP sheets offer a more effective reinforcement solution for enhancing stiffness and controlling deflection in concrete beams, especially in structures requiring high resistance to cracking and yielding.